Resuelve estas ecuaciones.
a) 2x + 5 - 3x + 7 = 4 (2x + 3)
b) 2 (3 + 3x) - 3 (1- 3x) = - 2
c) 5 (3 - 2x) - 10 = 4 (2 - 3x) + 6
d) 2 (3 + 3x) - 3 (1- 3x) - 7 (3 - 3x) = 0
e) 8 (3- 3x) - 12 - 9 (5 - x) = 12

1
b) x = - 1/3
c) x = 9/2
d) x = 1/2
e) x = -3
O.K GRACIAS

Respuestas

2013-12-15T16:06:48+01:00
A)
2x + 5 - 3x + 7 = 4 (2x + 3)
2x + 5 - 3x + 7 = 8x + 12
2x - 3x - 8x = 12 - 5 - 7
-9x = 0
-9x/-9 = 0/-9
x = 0

b)
2 (3 + 3x) - 3 (1- 3x) = - 2
6 + 6x - 3 + 9x = -2
6 - 3 + 2 = -6x - 9x
5 = -15x
5/-15 = -15x/-15
-1/3 = x

c) 
5 (3 - 2x) - 10 = 4 (2 - 3x) + 6
15 - 10x - 10 = 8 - 12x + 6
15 - 10 - 8 - 6 = -12x + 10x
-9 = -2x
-9/-2 = -2x/-2
9/2 = x

d)
2 (3 + 3x) - 3 (1- 3x) - 7 (3 - 3x) = 0
6 + 6x - 3 + 9x - 21 + 21x = 0
6 - 3 - 21 = -6x - 9x - 21x
-18 = -36x
-18/-36 = -36x/-36
1/2 = x 
 
e)
8 (3- 3x) - 12 - 9 (5 - x) = 12
24 - 24x - 12 - 45 + 9x = 12
24 - 12 - 45 - 12 = 24x - 9x
-45 = 15x
-45/15 = 15x/15
-3 = x
52 4 52